Navon-induced processing biases fail to affect the recognition of whole faces and isolated facial features. Issue 6 (18th August 2022) - Estudillo, Alejandro J.; Zheng, Bryan Leong Qi; Wong, Hoo Keat
ABSTRACT : According to the processing bias account, global Navon-induced processing primes the adoption of a holistic strategy whereas local Navon-induced processing triggers featural processing. As faces are recognised at a holistic level, global Navon-induced processing would increase recognition accuracy of whole faces. In contrast, local Navon-induced processing would enhance the recognition of individual facial features. In two experiments we explored this account using the part/whole task. Observers were asked to recognise facial features presented in isolation or embedded into whole faces, after global or local Navon-induced processing. In both experiments, results showed a whole-over-part advantage whereby facial features were recognised more accurately in the context of the whole face than in isolation. However, Navon-induced processing failed to modulate this effect as well as the magnitude of holistic-featural face processing. These results cast doubts on the reliability of Navon processing to prime the adoption of a particular processing style for face identification.